2009
DOI: 10.1097/cco.0b013e32832efc5b
|View full text |Cite
|
Sign up to set email alerts
|

Managing menopausal symptoms after gynecological cancer

Abstract: There is no evidence showing hormones negatively influence survival after treatment for epithelial ovarian, squamous cervical or vulvar cancer. Their use can be considered in symptomatic patients with endometrial cancer, after weighing the benefits against the risk of recurrence. Gynecologic cancer survivors suffering from menopausal symptoms should be supported by advice about the alternatives to hormonal replacement therapy and by giving them nonbiased information on the present knowledge on the effects of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
10
0
7
Order By: Relevance
“…24 Hormone replacement can be considered after weighing the potential and proven benefits with the theoretical risk of increased recurrence. 102 …”
Section: Discussionmentioning
confidence: 97%
“…24 Hormone replacement can be considered after weighing the potential and proven benefits with the theoretical risk of increased recurrence. 102 …”
Section: Discussionmentioning
confidence: 97%
“…(44) One small prospective clinical trial of ERT administered to ovarian cancer patients suggested that ERT was associated with prolonged survival. However, the study failed to stratify the patients by tumor ER expression either at enrollment or at time of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Водночас тривалий прийом КОК підвищує ризик розвитку раку шийки матки. Результа-ти новітніх експериментальних досліджень демонструють участь естрогенів у розвитку даного виду раку [76].…”
Section: менеджмент менопаузи в жінок із онкологічною патологіею в анunclassified